2013
DOI: 10.1007/s40261-012-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Fungal meningoencephalitis caused by Alternaria: a clinical case

Abstract: Cerebral phaeohyphomycosis is an infrequent infectious condition associated with a high mortality rate. The authors describe a very rare case that occurred in an immunocompetent 18-year-old man who developed severe meningoencephalitis and arachnoiditis caused by Alternaria alternata, which were diagnosed in the context of difficult-to-treat hydrocephalus. Etiological diagnosis was made based on fungal culture and histopathologic examination. Empirical treatment consisted of an early aggressive antifungal combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Up till date, only a few cases were reported on A. alternata infection in the brain. Silveira et al (2013) reported a fungal meningoencephalitis and arachnoiditis caused by A. alternata in an 18‐year‐old juvenile. He was immunocompetent at the time of diagnosis, with progressive and marked deterioration in the level of consciousness that evolved into coma and bilateral papilloedema (Silveira et al, 2013).…”
Section: Fungal Infection In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Up till date, only a few cases were reported on A. alternata infection in the brain. Silveira et al (2013) reported a fungal meningoencephalitis and arachnoiditis caused by A. alternata in an 18‐year‐old juvenile. He was immunocompetent at the time of diagnosis, with progressive and marked deterioration in the level of consciousness that evolved into coma and bilateral papilloedema (Silveira et al, 2013).…”
Section: Fungal Infection In Admentioning
confidence: 99%
“…Silveira et al (2013) reported a fungal meningoencephalitis and arachnoiditis caused by A. alternata in an 18‐year‐old juvenile. He was immunocompetent at the time of diagnosis, with progressive and marked deterioration in the level of consciousness that evolved into coma and bilateral papilloedema (Silveira et al, 2013). Another recent case reported by Cardona et al (2020) showed a cerebral phaeohyphomycosis in a 66‐year‐old man with initial asthenia, adynamia, mild dyspnoea, fever and disorientation.…”
Section: Fungal Infection In Admentioning
confidence: 99%
“…Alternaria species are mostly associated with hypersensitivity pneumonitis, bronchial asthma, allergic sinusitis and rhinitis (Shugar et al, 1981;Bush & Prochnau, 2004;Pant et al, 2005;Stark et al, 2005;Pulimood et al, 2007;Chowdhary et al, 2012). Less commonly, these fungi have been reported as causes of other infections including ocular infections (Laich et al, 2008;Konidaris et al, 2013), meningoencephalitis and arachnoiditis (Silveira et al, 2013), sinusitis (Pesic et al, 2015), granulomatous pulmonary disease (Lobritz et al, 1979), onychomycosis (Gianni et al, 1997;Romano et al, 2001), cutaneous infections (Lyke et al, 2001;Pereiro et al, 2004;Calabrò et al, 2008;Gomes et al, 2011;Brás et al, 2015) and subcutaneous infections (Kpodzo et al, 2011;Salido-Vallejo et al, 2014), and disseminated diseases (Kucan & Hall, 1985;Revankar et al, 2002). Among Alternaria spp., A. alternata has been the most frequently isolated species from all types of infections.…”
Section: Introductionmentioning
confidence: 99%